Unusual Appearance of a Cisternal Hydatid Cyst - Rumboldt, Zoran; Jednačak, Hrvoje; Talan-Hranilović, Jasna; Rumboldt, Tihana; Kalousek, Miljenko (American Journal of Neuroradiology, 2003)
Summary: We herein describe a case of an isolated multilocular hydatid cyst occurring in the basilar cisterns, with nondependent levels of different signal intensities shown on MR images. Three portions were visualized on T1-weighted images: the hyperintense inferior aspect, the isointense central part, and the superior aspect of lower signal intensity. The inferior portion was hypointense on T2-weighted images. This unusual appearance was caused by layering of hydatid sand and may represent a characteristic feature of hydatid disease.